Globalizing Higher Education in India: A step towards Multiculturalism - a Review - Sharma, Sunita Ramesh (Lingual Journal of Language and Culture; Vol 5 No 1 (2018)DO - 10.24843/LJLC.2018.v05.i01.p01, 2018)
Prime Minister Modi’s initiative “Educate in India” announced in May 2015, the objective is to attract international students and make India, a quality higher education hub in Asia. India aspires to transition from having the second highest student population leaving its shores to study abroad, to become a premier educational destination attracting more international students to its shores.   The paper reviews the growth of higher education system in India, draws inspirations from the experiences of other Asian countries and then reviews India’s piece of global cake. It also discusses the benefits of multiculturalism, which are going to flow in the Indian economy following Internationalization of higher education